Metabolic and behavioral adaptations of greater white-toothed shrews to urban conditions. (14th October 2020) - Oliveira, Flávio G; Mathias, Maria da Luz; Rychlik, Leszek; Tapisso, Joaquim T; von Merten, Sophie
Abstract: The global trend of urbanization is creating novel challenges for many animal species. Studies investigating behavioral differences between rural and urban populations often report a general increase in risk-taking behaviors in urban populations. According to the most common energy management model (the performance model), behaviors that increase access to resources, such as aggression and boldness, and behaviors that consume net energy, like locomotion and stress responses, are both positively correlated to resting metabolic rate (RMR). Thus, we expect urban populations to not only exhibit a higher level of risk-taking behavior but also a higher RMR. However, these interactions remain poorly investigated. Our main goal was to analyze the relationship between RMR and risk-taking behaviors in the greater white-toothed shrew ( Crocidura russula ) in rural versus urban populations. Trapped shrews were brought to captivity where we measured RMR, boldness, and exploration rate three times in each individual. Our findings revealed that urban shrews were indeed bolder and more exploratory, but contrary to our expectations, their RMR was lower than that of rural shrews. This is likely explained by differences in the environmental conditions of these two habitats, such as higher ambient temperatures and/or lower prey availability in cities. When looking at each population separately, this relationship remained similar: urban shrews with a higher RMR were less bold, and rural shrews with a higher RMR showed a lower exploration rate. We conclude that the energetic strategy of C. russula is dependent on the environmental and observational context and cannot be explained by the performance model. Abstract : Greater white-toothed shrews from the city are bolder and more explorative than rural shrews but have a lower metabolic rate. We tested if metabolic rate and behavioral performance were positively associated with shrews from both sites, a strategy commonly observed in other species. On the contrary, we found that, in both urban and rural shrew populations, individuals with a higher metabolic rate were shier and less explorative.